Kesetaraan Gender Egalitarianisme dalam Narasi Film Barbie melalui Perspektif Konstruktivisme - Pohan, Syafruddin; Yusuf, Febiola Aditya; Amalina, Febriani (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
The issue of gender equality is not something new today. This issue has been widely discussed in a series of interesting stories full of meaning, one of which is in the form of a film. This research explores the representation of gender equality in the Barbie film released in 2023 and directed by Greta Gerwig from a constructivist perspective. The Barbie film is mass media that influences people's perceptions of gender bias. In the context of constructivism, films are considered the result of construction by media professionals, which can strengthen or change gender stereotypes that already exist in society. The research method used is a qualitative approach with Roland Barthes' semiotic analysis. The constructivism paradigm is used to understand how reality is understood and constructed by research subjects. The research subject is the representation of gender equality in the Barbie film narrative, while the research object is the dialogues in the film that will be analyzed. The results of the analysis show that the Barbie film depicts excessive expectations placed on women and criticizes views that trivialize or simplify issues of gender equality. The conclusion of this research is that the Barbie film as part of mass media depicts gender equality issues in a complex way and triggers critical thinking about gender stereotypes in society.